Tumor Detection by Using Image Processing - Younis, Arshad Yassin Ghanem; Jassim Muhammad, Murad Abdul Qadir; Obaid Deeb, Mukhaled Awwad (Journal of Science in Medicine and Life, 2024)
Medical Imaging Techniques (MITs) are non-invasive methods for looking inside the body without opening up the body surgically. It used to assist diagnosis or treatment of different medical conditions. There are many medical imaging techniques; every technique has different risks and benefits. This paper presents a review of these techniques; concepts, advantages, disadvantages, and applications. The concerning techniques are; X-ray radiography, X-ray Computed Tomography (CT), Magnetic Resonance Imaging (MRI), ultrasonography. And (real time information and cost) will present.